Michel Monten's Style in His “Essays” - Absalamova Gulmira Sharifovna (Procedia of Social Sciences and Humanities, 2020)
This article discusses the methods and metaphors used by the author in “Essays” by Michel Montaigne, a lawyer and thinker who had a place in Renaissance French literature in the 16th century. In “Essays”, the writer wrote down his life experiences and the methods and metaphors his still is interesting and relevant today.